Performance and mechanisms for Cd(II) and As(III) simultaneous adsorption by goethite-loaded montmorillonite in aqueous solution and soil. (15th March 2023) - Zhao, Chenchen; Yao, Jun; Knudsen, Tatjana Šolević; Liu, Jianli; Zhu, Xiaozhe; Ma, Bo; Li, Hao; Cao, Ying; Liu, Bang
Abstract: A series of goethite-modified montmorillonite (GMt) materials was synthesized for the amelioration of cationic cadmium (Cd) and anionic arsenic (As) complex contaminants in soil and water bodies. The results showed that goethite (Gt) was successfully loaded onto the surface of montmorillonite (Mt), which possessed more functional groups (such as Fe–O, and Fe–OH) and a larger specific surface area. GMt-0.5 (Mt loaded with Gt at a ratio of 0.5:1) showed the highest adsorption capacity for Cd(II) and As(III) with the maximum of 50.61 mg/g and 57.58 mg/g, respectively. The removal rate of Cd(II) was highly pH dependent, while the removal rate of As(III) showed little dependence on pH. The goethite on montmorillonite might contribute to the formation of surface complexes with As(III) and oxidation of As(III) to As(V). In the binary system, both, synergistic and competitive adsorption existed simultaneously. Importantly, in the binary system, the removal of As(III) was more favorable because of the electrostatic interaction, formation of a ternary complex, and co-precipitation. In addition, the amendment of GMt-0.5 significantly reduced the availability of Cd and As in the soil. This study suggests that GMt-0.5 is a promising candidate for the simultaneous immobilization of metal (loid)s in both, aqueous solution and mine soil. Graphical abstract: Image 1 Highlights: GMt-0.5 has a great removal efficiency for Cd(II) and As(III). Higher adsorption capacity of GMt-0.5 for As(III) in both two systems. In the binary system, Cd(II) remarkably enhanced the removal of As(III) by GMt-0.5. Cd(II) induces As(III) to form ternary complexes and enhances As(III) adsorption. GMt-0.5 effectively immobilizes Cd and As in mine soil.